x/2 + 2y/3= -1, x- y/3= 3

Asked by  | 10th Apr, 2011, 03:29: PM

Expert Answer:

To solve the following equation:
x/2 + 2y/3= -1     .... (1) 
x- y/3= 3             .... (2)
Multiply both the first equations by 6 and the second by 3, we get
3x + 4y = -6      .... (3)
3x - y = 9          .... (4)
Subtracting equation (4) from (3), we get
5y = -15   =>  y = -3
Put y = -3 in equation (4),
3x - (-3) =9
=> 3x + 3 = 9
=> 3x = 6
=>   x = 2.
Hence x =2 and y = -3.

Answered by  | 10th Apr, 2011, 10:05: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.